Homines, Funera, Astra 3-4 Proceedings of the International Symposium on Funerary Anthropology, '1 Decembrie 1918' University (Alba Iulia, Romania). - Kogălniceanu, Raluca (Archaeopress, 2023)
Papers focus on two central topics regarding past funerary behaviour in Central and South-Eastern Europe: cremation, and cause and time of death. Six studies relate to prehistory, from the Neolithic to Iron Age. Three more papers focus on the Roman Age and the other four are dedicated to the Medieval period.